Still on air : producing television in small markets - Rowe, Yvette J.; White, Livingston A. (Livingston Andrew ), 1975- (Kingston, Jamaica : The University of the West Indies Press, 2018)
"Within small markets for television like Jamaica, where sustaining a show on air is affected by financial and other challenges, remaining on air for a long time becomes a key marker of a programme's success. Still on Air documents the historical, production and broadcast experiences of some of Jamaica's long-running television shows".
Includes bibliographical references (pages 235-238) and index.
NLJCols20082021
Keywords: Television -- Production and direction; Television -- Production and direction -- Jamaica; Television broadcasting -- Jamaica; Mass media -- Jamaica; Mass media; Television broadcasting; Television -- Production and direction; Jamaica